Sobrevivência aparente e ritmo anual (reprodução e muda) de Tolmomyias flaviventris (Aves) em um ambiente neotropical semiárido - Silva, Hélya Maria Santiago (2018)
In semiarid environments it is common for the reproductive period and the feathering to occur during the rainy season. Because they are activities of great energy expenditure and because they compete with other physiological activities, they affect the future chances of survival of the individuals. In this study, we sought to estimate demographic parameters and to relate them to temporal patterns of reproduction and feather-changing in Tolmomyias flaviventris (Wied, 1831), a passerine of the family Rhynchocyclidae (CBRO, 2015), in a fragment of Tropical Forest Seasonally Dry in northeastern Brazil. During the years 2013 to 2017 we performed 103 occasions of sampling using a standard protocol of capture-mark-recapture (CMR) recording the presence of incubation plate and change of feathers in the individuals. The CMR data of the last two years were converted into encounter histories for the execution of survival analysis and probability of recapture, using the Cormack-Jolly-Seber (CJS) formulation. During this period (2015 to 2017) the average rainfall of the region was around 400-500 mm being below expected. The results indicated that Tolmomyias flaviventris reproduced between the months of December and August, with a higher incubation plate concentration between January and June, these being the rainy months of the region. Moulting occurred between March and August, with a high overlap with the breeding period. This seems to be a common strategy of birds in semi-arid environments, aiming to better take advantage of the short period of greater availability of food. Estimates of apparent survival remained constant and low, around 20% per year, and did not vary according to the breeding and moulting periods. It is possible that the years of drought in the region may have affected survival. The apparent low survival may have been caused by scarce resources, characteristic of drought periods. The probability of recapture varied according to the molting period. The seedlings overlapped with the breeding period and were associated with the end of the rainy season when the availability of food for the insectivorous birds was low. In this way the low catch during the seedling period can be indicative of low activity of the individuals aiming at energy saving